The use of non-uniform sample phases for array synthesis - Azevedo, Joaquim Amândio R. (2019)
The non-uniformly sampling procedure and the Fourier transform properties permit to control the shape of an antenna array pattern. The problem found in this analysis is usually the appropriate use of the array factor phase for further control of the pattern. In this work, a new technique will be presented that provides the control of shaped beam patterns using also the phase of the nonequidistant samples of the array factor. Considering the phase, the ripple structure of an array pattern has more oscillations, which yields a function with a smaller transition region between the beam zone and the sidelobe zone. Another advantage of the phase usage is to obtain different array excitations that produce the same pattern amplitude.